Can a Nursing Home Psychotropic Reduction Project be Successfully Implemented in Assisted Living?. (September 2021) - Abrahamson, Kathleen; Davila, Heather; Kirk, Laura; Garavito, German Alarcon; Mueller, Christine
The objective of this study was to compare implementation of a psychotropic medication reduction project across two types of residential long-term care settings: nursing homes (NH) and assisted living (AL) facilities. Fifteen NHs and 14 AL facilities from within a single corporate chain participated in the psychotropic medication reduction project. Using a comparative case study approach, we conducted in-person and telephone interviews with 62 staff members from participating NH and AL facilities to investigate the experience of project implementation. Project implementation within the more institutional NH model produced dramatic changes in residents' lives and medication use. Conversely, changes made in the AL environment appeared to have less impact on resident medication use and resident-centric narratives, and AL staff identified numerous barriers to implementation. Identifying methods to monitor processes and outcomes of care without increasing the regulatory burden of AL facilities may increase transferability of quality improvement efforts across settings.